A Summary of Chinese Expert Consensus on Fetal Growth Restriction (An Update on the 2019 Version) - Fetal Medicine Subgroup, Chinese Society of Perinatal Medicine, Chinese Medical Association; Maternal-Fetal Medicine Committee, Chinese Society of Obstetrics and Gynecology, Chinese Medical Association; Luming Sun; Yali Hu; Hongbo Qi; Dandan Shi (Maternal-Fetal Medicine)
Abstract. Fetal growth restriction (FGR) is a common complication of pregnancy associated with higher rates of perinatal mortality and morbidity, as well as a variety of long-term adverse outcomes. To standardize the clinical practice for the management of FGR in China, Fetal Medicine Subgroup, Chinese Society of Perinatal Medicine, Chinese Medical Association and Maternal-Fetal Medicine Committee, Chinese Society of Obstetrics and Gynecology,Chinese Medical Association organized an expert committee to provide official consensus-based recommendations on FGR. We evaluated the evidence provided by relevant high-quality literature, performed a three-round Delphi study and organized face-to-face meetings with experts from multidisciplinary backgrounds. The consensus includes the definition, prenatal screening, prevention, diagnosis, monitoring and management of FGR.